2016
DOI: 10.1002/2015jd024285
|View full text |Cite
|
Sign up to set email alerts
|

Assessing spatiotemporal variation of drought in China and its impact on agriculture during 1982–2011 by using PDSI indices and agriculture drought survey data

Abstract: Inspired by concerns of the effects of a warming climate, drought variation and its impacts have gained much attention in China. Arguments about China's drought persist and little work has utilized agricultural drought survey area to evaluate the impact of natural drought on agriculture. Based on a newly revised self‐calibrating Palmer Drought Severity Index (PDSI) model driven with air‐relative‐humidity‐based two‐source (ARTS) E0 (PDSIARTS; Yan et al., 2014), spatial and temporal variations of drought were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…After 2000, a wetting trend ( p < 0.01) was obtained across China as a whole and especially in northern China. A drying trend was found for southern China until 2011 (Yan et al, , ), which supports our results that climate change had favoured the overall increase of GPP and plant growth in China and northern China except southern China since 2000. Note that annual P r decreased from 2000 to 2011 in southern China and then increased after 2011 (Figure ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After 2000, a wetting trend ( p < 0.01) was obtained across China as a whole and especially in northern China. A drying trend was found for southern China until 2011 (Yan et al, , ), which supports our results that climate change had favoured the overall increase of GPP and plant growth in China and northern China except southern China since 2000. Note that annual P r decreased from 2000 to 2011 in southern China and then increased after 2011 (Figure ).…”
Section: Discussionsupporting
confidence: 90%
“…Monthly incident global radiation ( Q ) and net radiation ( R n ) were calculated from sunshine hour according to the Food and Agriculture Organization (FAO) method (Allen et al, ). The FAO R n method has been evaluated against observations at the Qianyanzhou flux tower site in southern China and then further applied to drought research in China (Yan et al, , 2016b).…”
Section: Datasets and Processing Proceduresmentioning
confidence: 99%
“…Similarly, Yan et al . () found that drought area (drought severity) shows a significant increasing trend (decreasing trend) during 1982–2011, based on PDSI by using both Thornthwaite and Penman–Monteith methods. In terms of identifying drought events, a significant upward trend in the number of drought events has been found, which is different from that by Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many drought indices have been developed to monitor drought evolution on region and global scales (Yan et al, 2016).…”
mentioning
confidence: 99%
“…The precipitation-runoff relationship (PPR) is an important issue in engineering hydrology, water resource planning and management, and watershed system evolution (Guo et al, 2016;Nourani et al, 2015). The focus of current researches involving the change and transformation process of the precipitation-runoff relationship.…”
mentioning
confidence: 99%